What are the characteristics of asthma patients with elevated serum IgG4 levels?. (March 2016) - Flament, T.; Marchand-Adam, S.; Gatault, P.; Dupin, C.; Diot, P.; Guilleminault, L.
Abstract: Introduction: IgG4 has recently been a subject of great interest in human pathology. No data are available about the characteristics of asthma patients with elevated IgG4 levels. Population and methods: An observational study was conducted from January 2006 to March 2015 in a difficult-to-treat population of asthma patients. Twenty-six difficult-to-treat asthma patients with elevated serum IgG4 levels (IgG4/IgG ratio up to 10%) were compared with a control population of 98 difficult-to-treat asthma patients with normal serum IgG4. Blood eosinophilia, total IgE and FeNO were compared between groups to better characterize asthma patients with elevated serum IgG4 levels. Results: Median IgG4 concentrations were 1.72 g/l [1.19–2.36] and 0.22 g/l [0.10–0.49] in the elevated IgG4 group and normal Ig4 group, respectively. Median blood eosinophilia was more than three times higher in patients with elevated serum IgG4 levels than in controls (0.75 10 9 /L [IQR 0.54–1.78] vs 0.22 10 9 /L [IQR 0.09–0.54] respectively, p < 0.0001). Total IgE was twice as high (264.5 kUI/l [IQR 166.3–779] vs 126 kUI/l [IQR 26–350] respectively; p < 0.05) and FeNO was nearly twice as high (61 [IQR 41–111] ppb vs 35 [IQR 23–51] ppb, p < 0.001). Allergic broncho-pulmonary aspergillosis (ABPA) and eosinophilic granulomatosis with polyangiitis (EGPA) were observed in the asthma patients with elevated serum IgG4. Ten patients had unexplained increased blood eosinophilia. Conclusion: Asthma patients with elevated IgG4 levels have significantly higher blood eosinophilia, total IgE and FeNO. ABPA and EGPA are observed in patients with elevated serum IgG4. Highlights: Characteristics of asthma patients with elevated serum IgG4 is studied. Marker of type 2 inflammation is low in these patients. High proportion of patients had unexplained increased blood eosinophilia.